2008
DOI: 10.1161/circulationaha.108.770917
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS as a Marker of Conduction Abnormality and a Predictor of Prognosis of Brugada Syndrome

Abstract: Background— Conduction abnormalities serve as a substrate for ventricular fibrillation (VF) in patients with Brugada syndrome (BS). Signal-averaged electrograms can detect late potentials, but the significance of conduction abnormalities within the QRS complex is still unknown. The latter can present as multiple spikes within the QRS complex (fragmented QRS [f-QRS]). We hypothesized that f-QRS could indicate a substrate for VF and might predict a high risk of VF for patients with BS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
294
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(313 citation statements)
references
References 29 publications
8
294
0
6
Order By: Relevance
“…[2][3][4][5][6][7][8] Mutations in SCN5A, which encodes the pore-forming subunit of the cardiac voltage-gated sodium channel, have been associated with the major form of BrS (BrS1) in approximately 20% of cases. [9][10][11] The clinical severity of BrS may vary with the responsible genes and/or mutation sites, although the genotypephenotype relationship remains poorly characterized. The presence of SCN5A mutations is not related to the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Mutations in SCN5A, which encodes the pore-forming subunit of the cardiac voltage-gated sodium channel, have been associated with the major form of BrS (BrS1) in approximately 20% of cases. [9][10][11] The clinical severity of BrS may vary with the responsible genes and/or mutation sites, although the genotypephenotype relationship remains poorly characterized. The presence of SCN5A mutations is not related to the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…marker of depolarization abnormality and myocardial scar in patients with coronary artery disease (Varriale and Chryssos 1992;Das et al 2006;Michael et al 2007;Das et al 2009). Additionally, fQRS has been demonstrated as a marker of increased mortality and arrhythmic events in patients with ischemic cardiomyopathy ), arrhythmogenic right ventricular dysplasia/cardiomyopathy (Peters et al 2008) and Brugada syndrome (Morita et al 2008). More importantly, it has been shown that the presence of fQRS in ≥2 contiguous leads predicts myocardial scar in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that such fractionated QRS may have some relationship with their arrhythmic events in patients with type 1 ECG (Morita et al 2008). Other study also showed that right ventricular conduction is delayed in patients with Brugada syndrome (Tukkie et al 2004).…”
Section: Late Potentials By Sa-ecgmentioning
confidence: 95%
“…patients with type 1 ECG could show fractionated QRS as a result of conduction abnormality (Morita et al 2008). A recent report showed that such fractionated QRS may have some relationship with their arrhythmic events in patients with type 1 ECG (Morita et al 2008).…”
Section: Late Potentials By Sa-ecgmentioning
confidence: 99%